2020
DOI: 10.3389/fimmu.2020.00686
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Enteritidis Effector AvrA Suppresses Autophagy by Reducing Beclin-1 Protein

Abstract: Autophagy is a cellular process to clear pathogens. Salmonella enterica serovar Enteritidis (S.E) has emerged as one of the most important food-borne pathogens. However, major studies still focus on Salmonella enterica serovar Typhimurium. Here, we reported that AvrA, a S. Enteritidis effector, inhibited autophagy to promote bacterial survival in the host. We found that AvrA regulates the conversion of LC3 I into LC3 II and the enrichment of lysosomes. Beclin-1, a key molecular regulator of autophagy, was decr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Autophagy is a catabolic process in which autophagosomes is formed, and it has double-sided effect in cancer proliferation and death [21,22]. LC3 and Beclin-1 are key molecular regulator of autophagy and can be used as autophagy marker [23,24]. To investigate whether CYT997 could trigger autophagy in GC cells, Lyso-Tracker Red, a membrane acidotropic dye probe was used to mark cellular acidic organelles (AVOs), such as lysosomes and autolysosomes.…”
Section: Cyt997 Triggers Protective Autophagy In Gc Cellsmentioning
confidence: 99%
“…Autophagy is a catabolic process in which autophagosomes is formed, and it has double-sided effect in cancer proliferation and death [21,22]. LC3 and Beclin-1 are key molecular regulator of autophagy and can be used as autophagy marker [23,24]. To investigate whether CYT997 could trigger autophagy in GC cells, Lyso-Tracker Red, a membrane acidotropic dye probe was used to mark cellular acidic organelles (AVOs), such as lysosomes and autolysosomes.…”
Section: Cyt997 Triggers Protective Autophagy In Gc Cellsmentioning
confidence: 99%
“…Autophagy is an important component of the innate immune system in host anti-bacterial defense, which is known to target a population of Salmonella for degradation and restrict Salmonella replication (27,28). Beclin 1 interacts with several cofactors (e.g., Atg14L, HMGB1, IP3R and PINK) to promote the formation of Beclin 1-Vps34-Vps15 core complexes, thereby inducing autophagy (9). LC3, a mammalian homolog of yeast Atg8, is known to serve as a widely used marker for autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…But the pathogens have developed several survival mechanisms to prevent this degradation event (7). S. Typhimurium, including its effectors, has evolved to block host signaling cascades or even create favorable conditions for self-replication and survival by virtue of autophagy through specific mechanisms, so as to resist the host defense (8,9). It has been reported that spvC is responsible for the anti-inflammatory effect of S. Typhimurium to facilitate bacterial dissemination, and the host can eliminate intracellular bacteria by autophagy, which can inhibit the further spread of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Although Beclin-1 is a key regulator for autophagy and apoptosis, activation of autophagy induces an increased expression of the anti-inflammatory cytokine IL-10 and decreases the expression of IL-8 and TNF-α [ 21 ]. It is reported that S. Enteritidis AvrA inhibits autophagic response by decreasing the Beclin-1 concentration, which may be associated with the JNK/AP-1 signaling pathway [ 22 ]. In our study, deficiency of SP-AvrA in S. Pullorum C79-13 caused the upregulation of Beclin-1 and p-JNK in infected HeLa and Caco2 BBE cells, suggesting that SP-AvrA may control autophagy in the anti-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%